2018
DOI: 10.3389/fpubh.2018.00280
|View full text |Cite
|
Sign up to set email alerts
|

Implementation Climate and Time Predict Intensity of Supervision Content Related to Evidence Based Treatment

Abstract: Objective: Children infrequently receive evidence-based treatments (EBTs) for mental health problems due to a science-to-practice implementation gap. Workplace-based clinical supervision, in which supervisors provide oversight, feedback, and training on clinical practice, may be a method to support EBT implementation. Our prior research suggests that the intensity of supervisory focus on EBT (i.e., thoroughness of coverage) during workplace-based supervision varies. This study explores predictors of supervisor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 73 publications
(99 reference statements)
0
7
0
Order By: Relevance
“…Across both samples, scores on the EBCSS subscales demonstrated acceptable internal consistency and evidence of structural validity. Construct validity evidence was generated in aim 1 by showing that scores on the EBCSS subscales were higher in agencies with higher levels of EBP implementation climate, an outcome supported by theory and prior research [28]. Aim 2 provided construct validity evidence.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Across both samples, scores on the EBCSS subscales demonstrated acceptable internal consistency and evidence of structural validity. Construct validity evidence was generated in aim 1 by showing that scores on the EBCSS subscales were higher in agencies with higher levels of EBP implementation climate, an outcome supported by theory and prior research [28]. Aim 2 provided construct validity evidence.…”
Section: Discussionmentioning
confidence: 89%
“…The ICS assesses the extent to which clinicians share perceptions that they are expected, supported, and rewarded to use EBP in their clinical work with clients. Scores on the ICS have demonstrated excellent reliability and evidence of construct-related validity [49][50][51][52], including positive associations with EBP-related content in clinical supervision [28]. Items were rated on a Likert-type scale from 0 ("not at all") to 4 ("a very great extent").…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An important future direction is to explore characteristics of the setting, supervisor, clinician, and session that may influence the selection or elicitation of a particular approach. Related studies have largely failed to identify clinician or supervisor characteristics that influence practice, but have found that either the organizations’ climate toward EBTs ( 57 , 58 ) or being situated within a private vs. public agency ( 18 ) influence supervision practice. Nonetheless, numerous factors could plausibly influence supervisors’ technique use.…”
Section: Discussionmentioning
confidence: 99%
“…The ICS has also shown positive correlations with implementation outcomes, such as knowledge and attitudes toward EBPs [ 11 , 17 ], intensity of supervisory focus on evidence-based treatment [ 6 ], and clinicians’ use of EBPs [ 11 ]. As measuring actual use of EBPs is challenging [ 18 ], measuring clinicians’ intention to use newly learned EBP can be a good alternative, as intentions are proposed to be determinants of behavior [ 19 21 ] and thus important when making a decision to adopt EBPs.…”
Section: Introductionmentioning
confidence: 99%